Standing Tall: How Plant Nutrition Can Prevent Crops from Falling Down - Banoth, Sai Kumar; Kasbe, Sudhanshu S.; Imran, G. M.; Lakshman, Bharothu; Susmitha, S.; Sindhuja, S. (Chronicle of Bioresource Management, 2026)
Crop lodging is a serious constraint that adversely affects yield, quality and harvestability of cereal crops. Crop lodging refers to a condition in which crop stems or root systems lose their upright stature. High nitrogen fertilization leads to accelerated vegetative phase development, but with low rigidity, whereas low application of phosphorus and potassium leads to poor root and tissue solidity. In addition to those mentioned, other micronutrients, such as calcium, silicon, boron and copper, also play a critical role within cell walls. Proper control of lodging can be achieved by combining balanced fertilizer application with the timeliness of fertiliser application, growing lodging-resistant crops, optimising crop population, ensuring good drainage and making strategic applications of growth regulators. Therefore, a clearer understanding of scientifically relevant nutrient management practices is essential to improve crop rigidity and yield sustainability.